The biochemical analysis of southern African rhinoceros populations - O'Ryan, Colleen (Division of Chemical Pathology, 2018)
The drastic decline in the numbers of the five extant species of rhinoceroses world-wide, mainly as a result of poaching, have placed these species in imminent danger of extinction. This emphasizes the need to understand the relationships among the different species of rhinoceros. The advances in molecular biology have allowed the application of DNA-based genetic techniques to address a number of aspects of rhinoceros biology which have both academic interest and practical value to conservation management. There are four aspects to this study: Firstly, restriction endonuclease maps of mitochondrial DNA were constructed to estimate the time of divergence of Diceros bicornis (black rhinoceros) and Ceratotherium simum (white rhinoceros) from their common ancestor. Secondly, a population genetic study of the relationships among four subspecies of D. bicornis. Thirdly, the application of DNA fingerprinting to examine the intra- and inter-population relatedness in D. bicornis populations. Fourthly, a practical application of PCR to identify the origin of an unknown sample of DNA.